Optimizing the Composition of Basalt and Heat Treatment of Fly Ash-Based Mullite Ceramics Using the Taguchi Method - Tumpal Ojahan Rajagukguk; Anang Ansori; Ferdy - Ardiyansyah; Yusup Hendronursito (Department of Physics, Sebelas Maret University, 2024)
The development of industrial activities has an impact on the increase in waste produced, and fly ash, aluminum dross, and basalt dust are no exception. This research studies the potential of these three materials as ceramic materials. Basalt dust from East Lampung was used as filler. The effect on the physical and mechanical properties of mullite (3Al2O3-2SiO2) ceramics was studied. The manufacture of mullite ceramics based on Taguchi design includes fly ash compositions of 40%, 50%, and 60% and basalt content of 0%, 5%, and 10%. sintering temperatures of 600°C, 900°C, and 1,200°C. Taguchi and Anova were used to determine the effect of independent variables on hardness and density. In addition, macro and microphoto tests were carried out to determine the physical and topographic changes of mullite ceramics. Chemical composition tests with X-ray fluorescence were carried out on raw materials and ceramics that have been formed. Changes in the crystal phase in mullite ceramics were studied through the X-ray diffragment test. XRF test results obtained for raw fly ash (SiO2 + Al2O3 + Fe2O3): 84.84 wt%. The composition of raw basalt is predominantly 48.42% SiO2, 18.82% Al2O3, 12.60% Fe2O3, and raw aluminum dross with 67.821% Al2O3 content. The mullite ceramic specimen consists of 38.24–45.30% SiO2, 34.72–48.73% Al2O3, 6.3–9.99% Fe2O3, and 2.31–5.31% CaO. The crystal phases formed are mullite, pyroxene, and diopside. Analysis of variance shows that hardness is significantly affected by sintering temperature, with a P-value of 0.013 and a contribution of 93.77%. This modeling is acceptable with an error value of 1.26%, or R-sq: 98.74%. The addition of basalt increases the density of mullite ceramics, with a P-value of 0.033 and a contribution of 96.05%. The addition of basalt as a filler is not able to increase the hardness significantly, but it affects the higher ceramic density value. However, the formation of mullite is interesting to study further as a refractory material